Interobserver and Intraobserver Reliability in Sonoelastographic Assessment of Thyroid Nodules. Issue 1 (3rd March 2023) - Duman, Emrah; Aslan, Ahmet; Buz, Aysenur; Sancak, Seda; Aslan, Mine; Kabaalioglu, Adnan; Fersahoglu, Ayse Tuba; Okuroglu, Nalan; Onur, Ender
Abstract : Background: Thyroid ultrasonography is the first and perhaps most fundamental step for the radiological distinction of benign and malignant nodules. In this study, 2 radiologists reviewed the sonoelastographic and Doppler images of thyroid nodules and evaluated for the intraobserver and interobserver reliability. Purpose: We aimed to determine confusing nodule identifiers and sonographic features differently defined by observers. Methods: A total of 157 nodules in 91 patients (male/female, 72:19) with ages ranging from 18 to 72 years old were included in the study. Ultrasonographic images and video clips of the nodules were obtained and presented to 2 reviewers unaware of the cytopathology results. Two observers defined the characteristics of the nodules based on previously determined criteria. Then, intraobserver and interobserver correlation coefficients were calculated for each subcategory. Results: In the grayscale ultrasonographic examination, varying degrees from low to high interobserver correlation coefficients were obtained for different subcategories (between κ = 0.359 and κ = 0.821). In color Doppler examination, we obtained medium correlation coefficients ( κ = 0.493 and κ = 0.553). On the other hand, there was a high correlation coefficient in tissue compression elastography ( κ = 0.617 and κ = 0.638). According to our study results, elastographic pattern, shape of the nodule, presence of echogenic foci, and pathological lymph nodes are better predictors to determine the malignant potential of thyroid nodule with higher interobserver correlation. Therefore, these criteria may be used primarily for the evaluation of thyroid nodules. The intraobserver correlation coefficient was higher in the practitioner with longer experience, suggesting the importance of professional practice period on the decision-making process.